Pencil-like Hollow Carbon Nanotubes Embedded CoP-V4P3 Heterostructures as a Bifunctional Catalyst for Electrocatalytic Overall Water Splitting - Haiyang Chang; Zhijian Liang; Kun Lang; Jiahui Fan; Lei Ji; Kejian Yang; Shaolin Lu; Zetong Ma; Lei Wang; Cheng Wang (Nanomaterials, 2023)
Electrocatalytic water splitting is one of the most efficient ways of producing green hydrogen energy. The design of stable, active, and efficient electrocatalysts plays a crucial role in water splitting for achieving efficient energy conversion from electrical to hydrogen energy, aimed at solving the lingering energy crisis. In this work, CNT composites modified with CoP-V4P3 composites (CoVO-10-CNT-450P) were formed by carbonising a pencil-like precursor (Co3V2O8-H2O) and growing carbon nanotubes in situ, followed by in situ phosphorylation on the carbon nanotubes. In the HER electrocatalytic process, an overpotential of only 124 mV was exhibited at a current density of 10 mA cm−2. In addition, as an OER catalyst, a low overpotential of 280 mV was attained at a current density of 10 mA cm−2. Moreover, there was no noticeable change in the performance of the catalyst over a 90 h test in a continuous total water splitting experiment. The unique electronic structure and hollow carbon nanotube structure of CoVO-10-CNT-450P effectively increased the catalytic active sites, while also significantly improving the electrocatalytic activity. This work provides theoretical guidance for the design and synthetic route of high-performance non-precious metal electrocatalysts, and actively promotes the commercial application of electrochemical water splitting.